Review and Discussion of The Co(te)lette Film - Guy, Priscilla (The International Journal of Screendance, 2014)
In 2010, English director Mike Figgis presented The Co(te)lette Film, a cinematographic adaptation of eponymous live performance by Dutch choreographer Ann Van den Broek, Co(te)lette (2007). At the beginning of the film, the camera shows three women on all fours at the centre of a large podium. From the very first shots, the viewer is given exquisite high definitions images and close ups of these gorgeous women and their more intimate body parts as they move frenetically and breath heavily. The synopsis of the film states: “There is no confrontation, nor rivalry. No story-telling, no solution and no ending. [The three women] grapple with the meaning and physical translation of beauty and perishability, rawness and fragility. The dancers are slaves of their own desires while trying to get in control of them.”